A comprehensive multi-omics analysis uncovers the associations between gut microbiota and pancreatic cancer - Han, Yang; Cao, Biyang; Tang, Jiayue; Wang, Jing (Frontiers in Microbiology, 2025)
Pancreatic cancer is one of the most lethal malignant neoplasms. Pancreatic cancer is related to gut microbiota, but the associations between its treatment and microbial abundance as well as genetic variations remain unclear. In this study, we collected fecal samples from 58 pancreatic cancer patients including 43 pancreatic ductal adenocarcinoma (PDAC) and 15 non-PDAC, and 40 healthy controls, and shotgun metagenomic sequencing and untargeted metabolome analysis were conducted. PDAC patients were divided into five groups according to treatment and tumor location, including treatment-naive (UT), chemotherapy (CT), surgery combined with chemotherapy (SCT), Head, and body/tail (Tail) groups. Multivariate association analysis revealed that both CT and SCT were associated with increased abundance of Lactobacillus gasseri and Streptococcus equinus. The microbial single nucleotide polymorphisms (SNPs) densities of Streptococcus salivarius, Streptococcus vestibularis and Streptococcus thermophilus were positively associated with CT, while Lachnospiraceae bacterium 2_1_58FAA was positively associated with Head group. Compared with Tail group, the Head group showed positive associations with opportunistic pathogens, such as Escherichia coli, Shigella sonnei and Shigella flexneri. We assembled 424 medium-quality non-redundant metagenome-assembled genomes (nrMAGs) and 276 high-quality nrMAGs. In CT group, indole-3-acetic acid, capsaicin, sinigrin, chenodeoxycholic acid, and glycerol-3-phosphate were increased, and the accuracy of the model based on fecal metabolites reached 0.77 in distinguishing healthy controls and patients. This study identifies the associations between pancreatic cancer treatment and gut microbiota as well as its metabolites, reveals bacterial SNPs are related to tumor location, and extends our knowledge of gut microbiota and pancreatic cancer.